(untitled) (Contemporary Journal of Social Science Review, 2025)
This study explores the intersection of linguistics and cultural expressions in British and Pakistani novels, analyzing how language constructs, negotiates and reflects cultural identity. Through a comparative linguistic lens, the researchers investigate stylistic choices, multilingualism and discourse structures that narrate cultural experiences and societal norms in these distinct literary traditions. The study employs a qualitative, comparative thematic analysis of the selected novels from both Pakistani English literature (novels) and British English Literature (novels) to examine the interaction of cultural legacy, colonial history, migration, and modernity. The research reveals how the selected novels express personal and societal battles for self-definition by examining common themes, such as belonging, displacement, tradition vs. modernity, and the effects of globalization. The results indicate unique but interrelated paths for the formation of identities influenced by geographical, cultural, and historical factors. This approach enhances wider discussions in cross-cultural literary studies, highlighting fiction’s significance in promoting intercultural understanding and communication.